HUBUNGAN ANTARA TINGKAT PENGETAHUAN DAN SIKAP KELUARGA DENGAN KEKAMBUHAN PADA PASIEN SKIZOFRENIA DI RSJD SURAKARTA - Wulansih, Sri; Widodo, Arif (Jurnal Berita Ilmu Keperawatan, 2008)
The increasing relapsing of client schizophrenia is shown increate of counted average 1.440 patients at last two months in year 2007. Purpose this research is to know the relation of between knowledge and families attitude with the relapsing at patient schizophrenia in Psychiatric Hospital of Surakarta. This Research is conducted quantitatively. Method research of Cross Sectional. Research Variable composed by the free variable is level storey of knowledge and attitude of while variable tied by is relapsing of patient schizophrenia. Sample used by counted 50 respondents. Data collecting use the questioners. Technique analyzes the data by using Chi Square. From data analysis obtained by that from variable mount the knowledge indicate that there no relation between level storey of family knowledge with the relapsing of patient schizophrenia. This matter is visible from value probability of larger ones from level of significant from knowledge level storey is 5% (0,256>0,05) meaning Ho accepted. While from attitude variable indicate that there is relation between family attitudes by relapsing is patient schizophrenia. This matter is visible from probability value which is smaller than level of significant from attitude is 5% (0,041